Inter-Trieval and Cultural Communication by Medical Personnel to Patients in the Health Service Process - Br.Sembiring, Tamaulina; Ramadhani, Yunita (Formosa Journal of Science and Technology, 2024)
Medan is the capital of the province of North Sumatra, Indonesia. This city is the third largest city in Indonesia after DKI Jakarta and Surabaya and the largest city outside Java, as well as the largest on the island of Sumatra. This research aims to find out what strategies are used by doctors with patients from different cultures at Medan City Hospital, during the health service process. The method used in this research is a qualitative method with an ethnographic approach. The research results found that First, the intercultural communication process carried out by doctors and patients occurs in the form of verbal and non-verbal communication. Second, Barriers that occur in intercultural communication are language, perception, and cultural barriers. Third, the strategy used to overcome this obstacle is to use translators, patient education, studying the patient's culture and character, and outreach to villages.